Reinforcement of existing cast-iron structural elements by means of fiber reinforced composites = Wzmacnianie istniejących, żeliwnych elementów konstrukcyjnych za pomocą włóknokompozytów - Marcinowski, Jakub; Różycki, Zbigniew (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper deals with tubular, cast-iron columns which should be reinforced due to the planned new structural function of these elements. According to the requirements of the monument conservator the general appearance of columns should not be altered significantly. Reinforcement with an external, thin coating (sleeve or jacket) made of composite (carbon fibre reinforced polymer - CFRP) was proposed. Details of the proposed technique were presented.
Keywords: słupy żeliwne; wzmocnienie; powłoka kompozytowa; CFRP; badania nieniszczące; cast iron columns; reinforecement; composite jacket; destructive tests